The Influence of Using Illustrated Storybooks on Improving Reading Interest Among Elementary School Children - Nuralifah, Fika; Masyithoh, Siti (PGMI, STAI Miftahul Ula Nganjuk, 2025)
The use of illustrated storybooks has been proven effective in increasing reading interest among elementary school children. These books not only help students become more active and confident in learning but also enhance their reading skills and overall interest in reading. By combining text and visual illustrations, illustrated storybooks create a varied and effective learning experience for lower-grade students. As a valuable educational tool, the use of this medium supports the literacy development of elementary school children by motivating them to be more engaged in the learning process, particularly in reading activities. Students’ reading interest and motivation can be improved through the use of appealing and enjoyable illustrated storybooks.